2018
DOI: 10.1002/cmdc.201800147
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Biological Activity, and Structural Analysis of Lactam‐Constrained PTPRJ Agonist Peptides

Abstract: PTPRJ is a receptor-like protein tyrosine phosphatase mainly known for its antiproliferative and tumor-suppressive functions. PTPRJ dephosphorylates several growth factors and their receptors, negatively regulating cell proliferation and migration. We recently identified a disulfide-bridged nonapeptide, named PTPRJ-19 (H-[Cys-His-His-Asn-Leu-Thr-His-Ala-Cys]-OH), which activates PTPRJ, thereby causing cell growth inhibition and apoptosis of both cancer and endothelial cells. With the aim of replacing the disul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Before proceeding with cell assays, the stability of the most active compound ( 4 ), determined by enzymatic experiments, was evaluated in aqueous solution [ 48 ]. Compound 4 was incubated at 25 °C and 37 °C in PBS buffer at pH 7.0.…”
Section: Resultsmentioning
confidence: 99%
“…Before proceeding with cell assays, the stability of the most active compound ( 4 ), determined by enzymatic experiments, was evaluated in aqueous solution [ 48 ]. Compound 4 was incubated at 25 °C and 37 °C in PBS buffer at pH 7.0.…”
Section: Resultsmentioning
confidence: 99%
“…Side chain-to-side chain lactams have also been used with success in retaining activity as disulfide surrogates in various endogenous peptide hormones, such as human urotensin II, endothelin-1, and oxytocin, as well as in small disulfide-rich peptides, such as conotoxins and gomesin . Moreover, lactams between the side chains of C- and N-terminal residues have been used to enhance anticancer cell growth activity and improve stability in a peptide activator of protein tyrosine phosphatase receptor type J . In addition, a side chain-to-side chain lactam is featured in the melanocortin receptor agonist peptide medication bremelanotide (Vyleesi) for the treatment of premenopausal women with hypoactive sexual desire disorder …”
Section: Discussionmentioning
confidence: 99%
“…61 Moreover, lactams between the side chains of C-and N-terminal residues have been used to enhance anticancer cell growth activity and improve stability in a peptide activator of protein tyrosine phosphatase receptor type J. 62 In addition, a side chain-to-side chain lactam is featured in the melanocortin receptor agonist peptide medication bremelanotide (Vyleesi) for the treatment of premenopausal women with hypoactive sexual desire disorder. 63 Despite the significant application of side chain-to-side chain lactam constraints, few studies have examined influences on secondary structures other than helices.…”
Section: Conformational Analysis Of Lactam Analogues Usingmentioning
confidence: 99%
“…Have study reported demonstrate the epidermal-type lipoxygenase. Aloxe3 is a potentially novel effector of the therapeutic fasting response (Sala et al, 2018). The discus fish will damage the skin tissue of the parents when pecking, and the content of Aloxe3 is reduced during the feeding period, which is consistent with Aloxe3 leads to a large amount of skin permeability and water loss leading to death after birth (Fournier et al, 2019).…”
Section: Discussionmentioning
confidence: 91%